Clinical marker for Alzheimer disease pathology in logopenic primary progressive aphasia - Giannini, Lucia A A; Irwin, David J; McMillan, Corey T; Ash, Sharon; Rascovsky, Katya; Wolk, David A; Van Deerlin, Vivianna M; Lee, Edward B; Trojanowski, John Q; Grossman, Murray (Neurology, 2017)
To determine whether logopenic features of phonologic loop dysfunction reflect Alzheimer disease (AD) neuropathology in primary progressive aphasia (PPA). We performed a retrospective case-control study of 34 patients with PPA with available autopsy tissue. We compared baseline and longitudinal clinical features in patients with primary AD neuropathology to those with primary non-AD pathologies. We analyzed regional neuroanatomic disease burden in pathology-defined groups using postmortem neuropathologic data. A total of 19/34 patients had primary AD pathology and 15/34 had non-AD pathology (13 frontotemporal lobar degeneration, 2 Lewy body disease). A total of 16/19 (84%) patients with AD had a logopenic spectrum phenotype; 5 met published criteria for the logopenic variant (lvPPA), 8 had additional grammatical or semantic deficits (lvPPA+), and 3 had relatively preserved sentence repetition (lvPPA-). Sentence repetition was impaired in 68% of patients with PPA with AD pathology; forward digit span (DF) was impaired in 90%, substantially higher than in non-AD PPA (33%, < 0.01). Lexical retrieval difficulty was common in all patients with PPA and did not discriminate between groups. Compared to non-AD, PPA with AD pathology had elevated microscopic neurodegenerative pathology in the superior/midtemporal gyrus, angular gyrus, and midfrontal cortex ( < 0.01). Low DF scores correlated with high microscopic pathologic burden in superior/midtemporal and angular gyri ( ≤ 0.03). Phonologic loop dysfunction is a central feature of AD-associated PPA and specifically correlates with temporoparietal neurodegeneration. Quantitative measures of phonologic loop function, combined with modified clinical lvPPA criteria, may help discriminate AD-associated PPA.